Women's Legislative Leadership and Substantive Representation in the Retailing of the TPKS Law - Rafifrian Evandio; Cecep Hidayat (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Increasing women's representation in parliament is often assumed to be directly proportional to the birth of gender-responsive policies. This article challenges this assumption by analyzing women's legislative leadership in the enactment of the Sexual Violence Crime Law (TPKS Law) through the perspective of substantive representation. Different from previous studies that emphasize descriptive representation or the role of civil society advocacy, this article offers a novelty by positioning women's legislative leadership as institutional actors working through formal authority and legislative mechanisms. This research uses a qualitative approach with policy analysis methods, based on a documentary study of minutes of DPR RI meetings, institutional releases, and media coverage related to the TPKS Law legislative process. The analysis is conducted by linking empirical findings to Hanna Pitkin's indicators of substantive representation, including agenda management, political decision-making, policy outcomes, and leadership consistency. The research findings indicate that the enactment of the TPKS Law was the result of political actions and strategic decisions by DPR leaders who were able to maintain the continuity of legislation amidst ideological resistance. This article emphasizes that women's substantive representation is not inherent to gender identity but is mediated by institutional structures and formal authority in the legislative process.